2013
DOI: 10.1002/oby.20033
|View full text |Cite
|
Sign up to set email alerts
|

VAT=TAAT‐SAAT: Innovative anthropometric model to predict visceral adipose tissue without resort to CT‐Scan or DXA

Abstract: ObjectiveTo investigate whether a combination of a selected but limited number of anthropometric measurements predicts visceral adipose tissue (VAT) better than other anthropometric measurements, without resort to medical imaging.HypothesisAbdominal anthropometric measurements are total abdominal adipose tissue indicators and global measures of VAT and SAAT (subcutaneous abdominal adipose tissue). Therefore, subtracting the anthropometric measurement the more correlated possible with SAAT while being the least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 39 publications
(73 reference statements)
3
60
1
Order By: Relevance
“…Although waist circumference is often considered an anthropometric proxy for VAT, it cannot differentiate VAT from the less deleterious subcutaneous adipose tissue (SAT) in the abdomen (Despres, 2012; Ibrahim, 2010), and is more closely correlated to total body adipose tissue ( R 2 =0.85) than VAT ( R 2 =0.59) (Bouchard, 2007). Investigators have recently developed equations to predict VAT that simultaneously integrate various anthropometric dimensions such as body mass index (BMI) and circumferences of the waist and thigh to more accurately approximate measured VAT ( R 2 =0.80–0.84) (Eastwood et al, 2013; Neamat-Allah et al, 2014; Samouda et al, 2013). While larger waist circumference is a known predictor of premature mortality (Pischon et al, 2008), the VAT prediction equation has not been studied as a predictor of long-term health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although waist circumference is often considered an anthropometric proxy for VAT, it cannot differentiate VAT from the less deleterious subcutaneous adipose tissue (SAT) in the abdomen (Despres, 2012; Ibrahim, 2010), and is more closely correlated to total body adipose tissue ( R 2 =0.85) than VAT ( R 2 =0.59) (Bouchard, 2007). Investigators have recently developed equations to predict VAT that simultaneously integrate various anthropometric dimensions such as body mass index (BMI) and circumferences of the waist and thigh to more accurately approximate measured VAT ( R 2 =0.80–0.84) (Eastwood et al, 2013; Neamat-Allah et al, 2014; Samouda et al, 2013). While larger waist circumference is a known predictor of premature mortality (Pischon et al, 2008), the VAT prediction equation has not been studied as a predictor of long-term health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…While larger waist circumference is a known predictor of premature mortality (Pischon et al, 2008), the VAT prediction equation has not been studied as a predictor of long-term health outcomes. Therefore, we tested the hypothesis that VAT predicted with a validated anthropometric regression equation (i.e., apVAT) is associated with premature mortality among a large population-based sample of men and women of European descent living in the United States (Samouda et al, 2013). We also explored the discriminative capacity of apVAT versus BMI and waist circumference to prognosticate mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Our work was motivated by the fact that the classical anthropometric parameters usually used to predict VAT (such as Waist C or SAD) reflect in reality more TAAT (VAT + SAAT) than VAT (Figure ). In adults, our findings suggested the subtraction of proximal thigh circumference (Proximal Thigh C) from Waist C …”
Section: Introductionmentioning
confidence: 73%
“…In our previous study on adults, we showed that whenever we subtract a well correlated anthropometric measurement with subcutaneous abdominal adipose tissue (SAAT) while being the least correlated with VAT (given the fact that VAT had to be kept), from a well correlated anthropometric measurement with total abdominal adipose tissue (TAAT) which is the most correlated possible with VAT (with a view to keeping the maximal amount of VAT), we manage to predict VAT accurately in both men and women. We called this concept “VAT = TAAT − SAAT” . Our work was motivated by the fact that the classical anthropometric parameters usually used to predict VAT (such as Waist C or SAD) reflect in reality more TAAT (VAT + SAAT) than VAT (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation